2020
DOI: 10.1038/s41467-020-20230-z
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diversification of target genomic sites using processive base deaminase fusions blocked by dCas9

Abstract: In vivo mutagenesis systems accelerate directed protein evolution but often show restricted capabilities and deleterious off-site mutations on cells. To overcome these limitations, here we report an in vivo platform to diversify specific DNA segments based on protein fusions between various base deaminases (BD) and the T7 RNA polymerase (T7RNAP) that recognizes a cognate promoter oriented towards the target sequence. Transcriptional elongation of these fusions generates transitions C to T or A to G on both DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 59 publications
1
53
0
Order By: Relevance
“…Here, compared to other in vivo directed evolution systems in yeast ( 14 , 15 , 17 ), limitations of the current version of CRAIDE exist and need consideration and further improvement for the system to be applicable for efficient in vivo directed evolution across multiple species. Indeed, with a mutation rate in the order of 3.26 × 10 –6 per base, RNA-mediated repair of genomic contexts using variant RNA donors as demonstrated in this study is still 2–3 orders of magnitude less efficient compared to state-of-the-art in vivo directed evolution methods for bacteria, yeast, and mammalian cells, like OrthoRep, ICE and TRACE ( 11 , 14 , 16 , 17 , 49 ). This hampers the adoption of CRAIDE in its current design for evolution-guided and massively parallelized studies of complex genetic traits, such as metabolic pathway engineering, unless a high-throughput screening or selection method is available.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Here, compared to other in vivo directed evolution systems in yeast ( 14 , 15 , 17 ), limitations of the current version of CRAIDE exist and need consideration and further improvement for the system to be applicable for efficient in vivo directed evolution across multiple species. Indeed, with a mutation rate in the order of 3.26 × 10 –6 per base, RNA-mediated repair of genomic contexts using variant RNA donors as demonstrated in this study is still 2–3 orders of magnitude less efficient compared to state-of-the-art in vivo directed evolution methods for bacteria, yeast, and mammalian cells, like OrthoRep, ICE and TRACE ( 11 , 14 , 16 , 17 , 49 ). This hampers the adoption of CRAIDE in its current design for evolution-guided and massively parallelized studies of complex genetic traits, such as metabolic pathway engineering, unless a high-throughput screening or selection method is available.…”
Section: Discussionmentioning
confidence: 82%
“…Lastly, it should be mentioned that during the preparation of this study, three novel DNA-templated genome editing technologies were reported; prime editor, TRACE and T7-DIVA ( 7 , 11 , 16 ). Here, prime editor demonstrated RNA-mediated genome engineering using in vitro -edited donor-amended gRNAs (prime editing gRNAs) ( 7 ), while TRACE and T7-DIVA demonstrated that T7RNAP fused to base editors could be applied for continuous in vivo mutagenesis of target genes controlled by genomically integrated T7 promoters ( 11 , 16 ). Individually, these new technologies enable >10 –4 mutations per base in engineered T7pro-driven open reading frames sized up to 2 kb, and nuclease-deficient integration of mutant bases in a prime editor window of approximately 30 bases ( 7 , 11 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high processivity of RNA polymerases permits the mutation of kilobases of DNA without significant sequence limitations, such as the availability of PAM sequences or the need to synthesize and introduce multiple, custom sgRNAs for each gene of interest during each round of evolution. Multiple strategies to terminate T7 polymerase can be used to prevent unwanted mutagenesis downstream of the targeted region, 16,56 and installation of a second T7 promoter facing the opposite direction of the protein coding sequence allows for the introduction of both C➔T and G➔A mutations. 16 Moreover, fusion to other DNAdamaging enzymes, such as improved variants of the adenosine deaminases 52,53 and a related approach to induce C➔G transversions 57 are beginning to allow expansion of the mutational spectrum of these technologies, 56 as was also the case in the CRISPR systems.…”
Section: Processive Targeted Mutagenesismentioning
confidence: 99%
“…EvolvR was first developed in E. coli and has since been implemented in yeast (Tou et al, 2020); T7-DIVA and eMuta were developed in E. coli and no other platforms are yet published. Table 1 compares EvolvR (Halperin et al, 2018), T7-DIVA (Álvarez et al, 2020), andeMuta (Park andKim, 2021) with OrthoRep from a user's point of view and we briefly expand below on five key points. The CRAIDE system for yeast (Jensen et al, 2021) is not covered as it has a far lower mutation rate than the others.…”
Section: Other Continuous Directed Evolution Systemsmentioning
confidence: 99%